Induced Matter Theory of gravity from a Weitzenböck 5D vacuum and pre-big bang collapse of the universe - Romero, Jesús Martín (2013)
We extend the Induced Matter Theory of gravity (IMT) to 5D curved spacetimes by using the Weitzenböck representation of connections on a 5D curved spacetime. In this representation the 5D curvature tensor becomes null, so that we can make a static foliation on the extra non-compact coordinate to induce in the Weitzenböck representation the Einstein equations. Once we have done it, we can rewrite the effective 4D Einstein equations in the Levi-Civita representation. This generalization of IMT opens a huge window of possible applications for this theory. A pre-big bang collapsing scenario is explored as an example.